Student Learning Using Powtoon and PowerPoint Learning Media with a Contextual Teaching Approach - Kurniati; Sri Rejeki; Aliahardi Winata (Journal of Education Reseach and Evaluation, 2024)
As technological advances continue to develop, educators are challenged to create various forms of learning media. The presence of learning media in an educational process plays a vital role in increasing the effectiveness of communication and facilitating the delivery of knowledge by teachers to students, thus allowing teachers to be more creative and innovative in delivering content. This study aims to analyze the effectiveness of using Powtoon and PowerPoint as media tools by applying a contextual teaching approach to improve the learning outcomes of grade IX students. This study used a quantitative approach, with the research design being a post-test-only control group. The research subjects consisted of two classes, each composed of 27 students. Data collection methods used in this study include tests and questionnaires. The research instruments included a six-item test and a ten-question questionnaire. The experimental method involved applying Powtoon in one class and PowerPoint in the other, with both classes applying the contextual teaching approach. After the data was collected, it was analyzed using descriptive statistics and a t-test. The analysis that was conducted shows that there is a significant difference in learning outcomes between the two groups of students using PowToon and PowerPoint. Based on these results, PowerPoint and PowerPoint media are effective in student learning outcomes. The implication of this research is to design more effective learning strategies by utilizing appropriate learning media and to explore further the various aspects of using learning media.